2023
DOI: 10.3389/fimmu.2023.1197011
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of DBT suppresses the aggressiveness of renal clear cell carcinoma and correlates with immune infiltration

Abstract: Conventional therapy for kidney renal clear cell carcinoma (KIRC) is unpromising. The tumor microenvironment (TME) is intimately linked to the invasiveness of a variety of tumor forms, including KIRC. The purpose of this research is to establish the prognostic and immune-related significance of dihydrolipoamide branched chain transacylase E2 (DBT) in individuals with KIRC. In this investigation, we discovered that DBT expression was down-regulated in a range of human malignancies, and low DBT expression in KIR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 51 publications
1
1
0
Order By: Relevance
“…DBT has been characterized as a tumor suppressor that inhibits tumor progression and corrects lipid metabolism disorders through the DBT/ANXA2/ YAP axis-regulated Hippo signaling pathway in clear cell renal cell carcinoma (Miao et al 2023). DBT expression has also been recognized as an independent prognostic factor in kidney renal clear cell carcinoma, highly correlated with immunological checkpoints and targeted medications (Zhang et al 2023). In this study, a strong positive correlation was observed between DLAT and DBT expression levels in patients with LUAD.…”
Section: Discussionsupporting
confidence: 54%
“…DBT has been characterized as a tumor suppressor that inhibits tumor progression and corrects lipid metabolism disorders through the DBT/ANXA2/ YAP axis-regulated Hippo signaling pathway in clear cell renal cell carcinoma (Miao et al 2023). DBT expression has also been recognized as an independent prognostic factor in kidney renal clear cell carcinoma, highly correlated with immunological checkpoints and targeted medications (Zhang et al 2023). In this study, a strong positive correlation was observed between DLAT and DBT expression levels in patients with LUAD.…”
Section: Discussionsupporting
confidence: 54%
“…The CIBERSORT algorithm analysis implies that DBT may enhance anti-cancer immune responses in KIRC by activating M1 macrophages, mast cells, and dendritic cells, and concurrently reducing regulatory T cell activity. Lastly, DBT expression in KIRC has been found to have a strong association with immune checkpoints and the efficacy of targeted and immunotherapy drugs [ 52 ].…”
Section: Discussionmentioning
confidence: 99%